Introduction: Pluralism and the Engaged Humanities - Adesokan, Akin; Panaite, Oana (Research in African literatures, 2025)
[...]was her experience as a female African American academic teaching this great books seminar that she felt that her colleagues and students assumptions of her competency and responsibility bordered on theoretical or ideological perspectives that they had taken for granted. "Institutions," Julien submits toward the end of that essay, cannot discount the power of race and other such categories, their centrality and tenacity in ways of reading within and beyond the classroom. The book argues that the adaptation of oral narrative genres is not a necessary feature of the novel but is, rather, an arbitrary one that expresses an imaginative solution to aesthetic and ideological problems: manipulation of genre reflects an author's narrative goals and social and ideological visions. Against the grain of conventional wisdom in African literature, she demonstrates that the approach that sees the connection between oral tradition and the novel as a sign of continuity and authenticity is a response to the dominance of Eurocentric criticism equating the novel with the Westand orality with Africa.